Legal Assistance Related to Land Dispute Handling in Jogomerto Village, Nganjuk District - W. Yulianingsih; Aldira Mara Ditta C. P.; Tiara Widyaputri; Waluyo (Nusantara Science and Technology Proceedings)
The more advanced economic activities, the many problems over land involved in it, the expansion of these activities generally in the form of increasing numbers of buying and selling, leasing, inheritance, lending, and even the emergence of legal relations. with foreign people or legal entities. Disputes over land ownership arise because each party feels entitled to the land that is the object of the dispute. Related to the issue of land ownership rights which is one of the problems found in Jogomerto Village, Tanjunganom District, Nganjuk District from the initial data obtained by the lack of legal knowledge about land ownership rights raises a pretty basic problem by the village government to be resolved. The method of carrying out activities is carried out in three stages, namely preparation and briefing, implementation, and evaluation. Overall legal aid activities in the form of socialization of registration of land rights and training on village regulation making and the agreement were successful, the people of Jogomerto Village welcomed positively and were satisfied with the activities that were followed, increasing public awareness of the law. Implementation of Community Service is very useful for the government and the community, especially for the people of Jogomerto village who are not familiar with the procedure for registering land rights and making village regulations. It is hoped that this activity can always be held periodically so that it can help the village government and village communities in realizing a law-aware community, especially regarding land disputes.